2016
DOI: 10.5194/acp-16-4343-2016
|View full text |Cite
|
Sign up to set email alerts
|

The vertical distribution of volcanic SO<sub>2</sub> plumes measured by IASI

Abstract: Abstract. Sulfur dioxide (SO 2 ) is an important atmospheric constituent that plays a crucial role in many atmospheric processes. Volcanic eruptions are a significant source of atmospheric SO 2 and its effects and lifetime depend on the SO 2 injection altitude. The Infrared Atmospheric Sounding Interferometer (IASI) on the METOP satellite can be used to study volcanic emission of SO 2 using high-spectral resolution measurements from 1000 to 1200 and from 1300 to 1410 cm −1 (the 7.3 and 8.7 µm SO 2 bands) retur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 120 publications
3
71
1
Order By: Relevance
“…It is also consistent with retrievals from OMI (Theys et al, 2015) and MODIS (Realmuto and Berk, 2016). In contrast, the IASI retrievals reported in Carboni et al (2016) found that the transient SO 2 burden reached only up to 0.6 Tg SO 2 . We consider though that 0.9 Tg of SO 2 is the best estimate for the mass of SO 2 injected by the Sarychev eruption into the UTLS.…”
Section: The Cesm1(waccm)-carma Modelcontrasting
confidence: 33%
See 4 more Smart Citations
“…It is also consistent with retrievals from OMI (Theys et al, 2015) and MODIS (Realmuto and Berk, 2016). In contrast, the IASI retrievals reported in Carboni et al (2016) found that the transient SO 2 burden reached only up to 0.6 Tg SO 2 . We consider though that 0.9 Tg of SO 2 is the best estimate for the mass of SO 2 injected by the Sarychev eruption into the UTLS.…”
Section: The Cesm1(waccm)-carma Modelcontrasting
confidence: 33%
“…It is a spectrometer measuring infrared light spectra at nadir. Its primary goal is to assess temperature and water vapour content of the atmosphere, but it can also be used to retrieve the atmospheric concentrations of various gases, including SO 2 (Clarisse et al, 2008;Carboni et al, 2016). IASI provides global coverage twice a day, and its footprint ranges from circular (12 km diameter at nadir) to elliptical (up to 20 km by 39 km at the end of the swath).…”
Section: The Cesm1(waccm)-carma Modelmentioning
confidence: 99%
See 3 more Smart Citations